(untitled) (Scientific journal of the Fergana State University, 2025)
This article provides an in-depth overview of the stages involved in building a dependency parsing treebank for the Uzbek language. It outlines the five simplified but essential stages commonly adopted in international practice when constructing a hierarchical corpus for any language. These stages are as follows: Text selection; pre-processing (including the choice of tools and resources); annotation; documentation of language-specific guidelines and treatment of non-universal linguistic features; and finally, transliteration.